The dynamic causality between corporate social responsibility and corporate political activity: a panel vector autoregression approach - Horiguchi, Shinji; Lin, Woon Leong; Law, Siong Hook (Faculty of Economics and Management, Universiti Putra Malaysia, 2018)
The objective of this study is to assess the dynamic causality between corporate social responsibility (CSR) and corporate political activity (CPA). This research uses panel vector autoregression (VAR) model within the framework of generalized method of moments (GMM) with consideration to the time invariant characteristics of each organisation. Based on a sample of 100 World’s Most Admired Companies (WMAC) listed in Fortune between 2007 and 2016, this study provides empirical evidences that the CPA negatively affects the CSR, while enhanced CSR does not warrant an enhanced CPA. The findings of this study contradict the notion propounded by the hypothesis of virtuous circle which states that there is a positive relationship and mutual reinforcement between CSR and CPA.